The methanolic fraction of Centratherum anthelminticum seed downregulates pro-inflammatory cytokines, oxidative stress, and hyperglycemia in STZ-nicotinamide-induced type 2 diabetic rats. - Arya, A.; Cheah, S.C.; Looi, C.Y.; Taha, H.; Mustafa, Mohd Rais; Mohd, M.A. (2012)
This study aimed to ascertain the potential of Centratherum anthelminticum seeds methanolic fraction (CAMFs) for the management of type 2 diabetes and its associated complications. CAMFs was initially tested on Î²-TC6 cells for H2O2-induced nuclear factor-ÎºB (NF-ÎºB) translocation effects. The result displayed that CAMFs significantly inhibited NF-ÎºB translocation from cytoplasm into the nucleus, dose-dependently. Furthermore, a 12-week sub-chronic CAMFs study was carried out on streptozotocin (STZ)-nicotinamideâinduced type 2 diabetic rat model to evaluate glycemia, essential biochemical parameters, lipid levels, oxidative stress markers, and pro-inflammatory cytokines level. Our study result showed that CAMFs reduced hyperglycemia by increasing serum insulin, C-peptide, total protein, and albumin levels, significantly. Whereas, elevated blood glucose, glycated hemoglobin, lipids and enzyme activities were restored to near normal. CAMFs confirmed antioxidant potential by elevating glutathione (GSH) and reducing malondialdehyde (MDA) levels in diabetic rats. Interestingly, CAMFs down-regulated elevated tumor necrosis factor Î± (TNF-Î±), interleukin (IL)-1Î² and IL-6 in the tissues and serum of the diabetic rats. We conclude that CAMFs exerted apparent antidiabetic effects and demonstrated as a valuable candidate nutraceutical for insulin-resistant type 2 diabetes and its associated complications such as dyslipidemia, oxidative stress, and inflammation.